The effect of company size, funding decisions, and investment decisions on company value with dividend policy as moderating variables - Dina Indah Pertiwi; Suyanto Suyanto; Sri Lestari Prasilowati (KINERJA, 2023)
The purpose of this study was to examine the effect of company size, funding decisions, and investment decisions on company value with dividend policy as a moderating variable in companies listed on the Jakarta Islamic Index 30 (JII30) 2015-2021.The population used in this study are companies listed on the Indonesia Stock Exchange and included in the Jakarta Islamic Index 30, with an observation period from 2015 - 2021. The sample used in this study was 8 companies using the purposive sampling method.The data processing method used in this study is a causality test with regression analysis and moderated regression analysis using SPSS version 24. The independent variables in this study are company size based on LN Total Assets (X1), funding policy based on Debt to Equity Ratio (X2), and investment decisions based on Price Earning Ratio (X3). The moderating variable in this study is dividend policy (Z). The dependent variable in this study is the company value (Y). The results of this study indicate that company size has a significant negative effect on company value, funding decisions have a significant positive effect on company value, investment decisions have a significant positive effect on company value, and dividend policy does not strengthen the relationship between company size and company value. Dividend policy strengthens the relationship between decisions funding and corporate value. company value and dividend policy do not strengthen the relationship between investment decisions and company value.